Participative management in health care services - M. Muller (AOSIS, 1995)
The need and demand for the highest-quality management of all health care delivery activities requires a participative management approach. The purpose with this article is to explore the process of participative management, to generate and describe a model for such management, focusing mainly on the process of participative management, and to formulate guidelines for operationalisation of the procedure. An exploratory, descriptive and theory-generating research design is pursued. After a brief literature review, inductive reasoning is mainly employed to identify and define central concepts, followed by the formulation of a few applicable statements and guidelines. Participative management is viewed as a process of that constitutes the elements of dynamic interactive decision-making and problem-solving, shared governance, empowerment, organisational transformation, and dynamic communication within the health care organisation. The scientific method of assessment, planning, implementation and evaluation is utilised throughout the process of participative management.